Medical deserts in Spain—Insights from an international project - Dubas‐Jakóbczyk, Katarzyna; Gonzalez, Ana Isabel; Domagała, Alicja; Astier‐Peña, Maria Pilar; Vicente, Veronica Casado; Planet, Antonia‐Gema; Quadrado, Agueda; Serrano, Rosa Mari; Abellán, Isabel Serafina; Ramos, Alba; Ballester, Marta; Seils, Laura; et al. (John Wiley & Sons, 2024)
Introduction Medical deserts are a growing phenomenon across many European countries. They are usually defined as (i) rural areas, (ii) underserved areas or (iii) by applying a measure of distance/time to a facility or a combination of the three characteristics. The objective was to define medical deserts in Spain as well as map their driving factors and approaches to mitigate them. Methods A mixed methods approach was applied following the project “A Roadmap out of medical deserts into supportive health workforce initiatives and policies” work plan. It included the following elements: (i) a scoping literature review; (ii) a questionnaire survey; (iii) national stakeholders' workshop; (iv) a descriptive case study on medical deserts in Spain. Results Medical deserts in Spain exist in the form of mostly rural areas with limited access to health care. The main challenge in their identification and monitoring is local data availability. Diversity of both factors contributing to medical deserts and solutions applied to eliminate or mitigate them can be identified in Spain. They can be related to demand for or supply of health care services. More national data, analyses and/or initiatives seem to be focused on the health care supply dimension. Conclusions Addressing medical deserts in Spain requires a comprehensive and multidimensional approach. Effective policies are needed to address both the medical staff education and planning system, working conditions, as well as more intersectoral approach to the population health management.
Keywords: health care demand; health care supply; health planning; health workforce; medical desert; medically underserved area; fi=Julkisjohtaminen|en=Public Management|